PELATIHAN PEMANFAATAN IKAN HASIL TANGKAPAN SAMPINGAN (HTS) MENJADI PRODUK INOVATIF PENYEDAP NON MSG NU RASA - Novianti, Teni; Ekawati, Nurul; Henda Nugraha, Eulis; Anas Syauqi, Muhammad; Ruspendi, Ruspendi; Risvana, Ivan (Universitas Mataram, 2024)
Cirebon Maritime Vocational School is located in the Cirebon Coastal Area which is close to the Mundu Fish Landing Site (TPI) Cirebon Regency, where in this area there are by-catch fish (HTS) which have not been well utilized. The aim of this community service is to increase the use of HTS fish, especially low economic fish around the waters of Mundu Cirebon so that their use can be optimized by Partners in increasing the added value of fishery products into innovative Non MSG NU Rasa flavoring products. The training activity method used consists of the preparation stage, implementation stage (counseling, practice or demonstration), evaluation stage and mentoring stage. Training activities on the use of by-caught fish into innovative non-MSG NU Rasa flavoring products at the Cirebon Maritime Vocational School can not only increase the knowledge and skills of partners in producing innovative products by applying appropriate technological tools but can also increase motivation in entrepreneurship as a development of business incubation at the school.